'PhysioDirect' telephone assessment and advice services for physiotherapy: protocol for a pragmatic randomised controlled trial - Hopper Cherida; Hollinghurst Sandra; Hay Elaine; Hall Jeanette; Coast Jo; Calnan Michael; Bishop Annette; Foster Nadine E; Salisbury Chris; Grove Sean; Kaur Surinder; Montgomery Alan (BMC, 2009)
Abstract Background Providing timely access to physiotherapy has long been a problem for the National Health Service in the United Kingdom. In an attempt to improve access some physiotherapy services have introduced a new treatment pathway known as PhysioDirect. Physiotherapists offer initial assessment and advice by telephone, supported by computerised algorithms, and patients are sent written self-management and exercise advice by post. They are invited for face-to-face treatment only when necessary. Although several such services have been developed, there is no robust evidence regarding clinical and cost-effectiveness, nor the acceptability of PhysioDirect. Methods/Design This protocol describes a multi-centre pragmatic individually randomised trial, with nested qualitative research. The aim is to determine the effectiveness, cost-effectiveness, and acceptability of PhysioDirect compared with usual models of physiotherapy based on patients going onto a waiting list and receiving face-to-face care. PhysioDirect services will be established in four areas in England. Adult patients in these areas with musculoskeletal problems who refer themselves or are referred by a primary care practitioner for physiotherapy will be invited to participate in the trial. About 1875 consenting patients will be randomised in a 2:1 ratio to PhysioDirect or usual care. Data about outcome measures will be collected at baseline and 6 weeks and 6 months after randomisation. The primary outcome is clinical improvement at 6 months; secondary outcomes include cost, waiting times, time lost from work and usual activities, patient satisfaction and preference. The impact of PhysioDirect on patients in different age-groups and with different conditions will also be examined. Incremental cost-effectiveness will be assessed in terms of quality adjusted life years in relation to cost. Qualitative methods will be used to explore factors associated with the success or failure of the service, the acceptability of PhysioDirect to patients and staff, and ways in which the service could be improved. Discussion It is still relatively unusual to evaluate new forms of service delivery using randomised controlled trials. By combining rigorous trial methods with economic analysis of cost-effectiveness and qualitative research this study will provide robust evidence to inform decisions about the widespread introduction of PhysioDirect services. Trial registration Current Controlled Trials ISRCTN55666618